Fractional Versions of Hadamard-Type Inequalities for Strongly Exponentially α,h−m-Convex Functions - Shasha Li; Ghulam Farid; Atiq Ur Rehman; Hafsa Yasmeen (Journal of Mathematics)
In this article, we prove some fractional versions of Hadamard-type inequalities for strongly exponentially α,h−m-convex functions via generalized Riemann–Liouville fractional integrals. The outcomes of this paper provide inequalities of strongly convex, strongly m-convex, strongly s-convex, strongly α,m-convex, strongly s,m-convex, strongly h−m-convex, strongly α,h−m-convex, strongly exponentially convex, strongly exponentially m-convex, strongly exponentially s-convex, strongly exponentially s,m-convex, strongly exponentially h−m-convex, and exponentially α,h−m-convex functions. The error estimations are also studied by applying two fractional integral identities.